1990
DOI: 10.1111/j.1365-2141.1990.tb04355.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a combined storage medium for 7‐day storage of platelet concentrates and 42‐day storage of red cell concentrates

Abstract: Studies were carried out to examine whether a single additive solution could support both platelet and red cell storage. An ionically balanced electrolyte solution fortified with citrate, glucose and bicarbonate was used. This solution has previously been shown to provide good platelet viability with storage for up to 7 d. Optimization studies demonstrated that with adenine added to this solution (CSM), it also allowed for satisfactory preservation of in vitro red cell parameters for up to 49 d of storage. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…However, the latter study used a different storage pack for PCs stored at day 7. Other studies have tended to show a decrease in recovery and survival after 7 days of storage compared with 5 days of storage (Heaton et al ., 1990; Holme et al ., 1990). In PCs collected by apheresis techniques, two studies have shown average decreases in recovery of 15–30% and survival of 15–20% when stored for 7 days compared with when stored for 5 days (Slichter et al ., 2001; Dumont et al ., 2002).…”
Section: In Vivo Data On the Effect Of Extended Storage Of Platelet Cmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the latter study used a different storage pack for PCs stored at day 7. Other studies have tended to show a decrease in recovery and survival after 7 days of storage compared with 5 days of storage (Heaton et al ., 1990; Holme et al ., 1990). In PCs collected by apheresis techniques, two studies have shown average decreases in recovery of 15–30% and survival of 15–20% when stored for 7 days compared with when stored for 5 days (Slichter et al ., 2001; Dumont et al ., 2002).…”
Section: In Vivo Data On the Effect Of Extended Storage Of Platelet Cmentioning
confidence: 99%
“…The same group showed that there was a decrease in recovery and survival with increasing length of storage but that recovery and survival were higher in PCs stored in synthetic media (Holme et al ., 1990). However, one study has shown similar platelet recovery, but significantly lower platelet survival, in PCs stored in a novel additive solution, compared with plasma after 5 or 7 days of storage (Heaton et al ., 1990). Using an alternative PAS, Murphy et al .…”
Section: In Vivo Studies Comparing Platelet Concentrates Stored In Plmentioning
confidence: 99%
“…Twenty volunteers participated in this study. Each donor donated a unit of whole blood, and CPD-anticoagulated platelet concentrates (PC) were prepared as described previously (Holme et al, 1990). The PC were stored in second-generation gas-permeable platelet containers for 5 d at 22°C.…”
Section: Studg Designsmentioning
confidence: 99%
“…Different groups of donors were used for different storage intervals. Survival data from previously conducted studies were utilized for comparison (Holme et al, 1987(Holme et al, , 1990(Holme et al, , 1993. In some cases whole blood units were collected into standard CP2D anticoagulant (Miles Inc., Covina, Calif.).…”
Section: Studg Designsmentioning
confidence: 99%
See 1 more Smart Citation